Novel Nd–Mo co-doped SnO₂/α-WO₃ electrochromic materials (ECs) for enhanced smart window performance - Goei, Ronn (2022)
In an urbanized city, about a third of total electrical consumption is allocated for indoor lighting and air conditioning system in residential and commercial buildings. The majority of the worldwide energy generation comes from burning of non-renewable fossil fuel which is not sustainable in the long run. The use of smart windows technology may catalyze the effort to reduce energy consumption of building and houses. More than 50% of heat entering a building through windows originate from the solar radiation in the near infrared (NIR) region. This candidate smart window material must exhibit dual-band (visible and NIR) modulation that allows selective modulation of NIR heat without affecting visible light transmission. A good electrochromic material in this respect should possess high visible light transmission, high NIR modulation, fast switching between colored and bleached state, and good stability over prolonged usage. In this work, we propose a novel Nd–Mo co-doped SnO2/α-WO3 electrochromic materials (ECs). As compared to the traditional SnO2/α-WO3 ECs, our Nd–Mo co-doped SnO2/α-WO3 ECs exhibits up to 90% visible light transparency (at λ = 600 nm), 62% NIR modulation (at wavelength 1200 nm), high coloration efficiency (~200 cm2 C−1), fast switching time with only 31% electrochromic performance drop (vs 59% of undoped sample) after up to 1000 reversible cyclic test. The enhanced electrochromic performance comes from the presence of Nd–Mo co-dopants that limit the trapping of Li + ion within α-WO3 framework, reduce the extent of crystallization of α-WO3 layer and enhancement of the electronic conductivity by transferring their excess electron to the conduction band of the SnO2. To the best of the authors’ knowledge, the present composition of ECs offers one of the better candidate materials for electrochromic to be used as thermal management layers on smart windows application.